Research on the Path of Information Management for Piano Rooms in Colleges and Universities - Ying, Yutao (Journal of Educational Research and Policies, 2026)
With the continuous development of art education in universities, the piano room, as an important venue for music teaching and practice, has its management efficiency and service quality directly affecting teaching effectiveness. Traditional piano room management models face issues such as uneven resource allocation, low usage efficiency, and difficulties in supervision. However, with the iteration of informatization and intelligence, informatization management can achieve optimal allocation of piano room resources, real-time monitoring of usage processes, and scientific management decision-making by introducing modern information technology. This paper aims to explore feasible paths for the informatization management of university piano rooms, analyze its advantages and challenges, and propose corresponding implementation strategies, with the hope of providing reference for the reform of university piano room management.